Environmental Assessment of Alternatives for Biowaste Treatment in Mexico City - Chávez, Carolina Silva; Caro, Dario; Thomsen, Marianne (Frontiers in Energy Research, 2019)
This paper aims to determine the environmental performance of the current landfill gas management system (based on flaring) in Mexico City (Bordo Poniente) in comparison to the collection of biogas generated from solid waste through one of the most innovative technology implemented in Denmark (Aikan Tecnology), which produces biogas and digestate from waste. Two alternative scenarios are proposed in which the Aikan Technology is implemented in Bordo Poniente to replace the existing system (reference scenario) that involves landfilling inorganic waste and composting organic waste in Bordo Poniente with no biogas recovery. The biogas recovered through Aikan Technology is exploited to provide heat and electricity (Scenario 1) or biofuel for the transportation sector (Scenario 2). A comparative life cycle assessment (LCA) was performed to evaluate the environmental performances associated with all scenarios by evaluating the impact categories Climate Change, Fossil Depletion, and Cumulative Energy Demand. According to the waste capacity of Bordo Poniente, the implementation of the Aikan Technology would result in a total annual reduction of 0.14 and 0.08 Mt of CO2 eq for Scenario 1 and Scenario 2, respectively. Scenario 1 was also the best performing scenario with respect to fossil depletion (-52 kg oil eq ton-1 of organic waste) and cumulative energy demand (-3557 MJ ton-1 of organic waste). The implementation of Aikan Technology in Mexico City represents an important challenge and requires further research into its economic and political feasibility. When it comes to tackling global environmental problems, international agreements ascribe high importance to environmental technology transfer. This study represents a preliminary step in terms of environmental assessment and thus provides important information for policymakers attempting to achieve more sustainable management of solid waste in Mexico.